2021
DOI: 10.3390/medicina57050459
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, Depression Severity, and Circadian Rhythms Disturbances as Clinical Correlates of Duration of Untreated Illness in Affective Disorders

Abstract: Background and Objectives: Affective disorders, namely bipolar (BDs) and depressive disorders (DDs) are characterized by high prevalence and functional impairment. From a dimensional point of view, BDs and DDs can be considered as psychopathological entities lying on a continuum. A delay in treatment initiation might increase the burden associated with affective disorders. The aim of this study is to analyze the correlates of a long duration of untreated illness (DUI) in these conditions. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The BRIAN scale has been used to assess biological rhythms in patients with MDD [ 25 27 ]. Using this scale, researchers have observed that biological rhythm disruption is associated with the severity of depression [ 6 , 35 ]. However, to date, no research has examined the reliability and validity of the BRIAN scale in patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…The BRIAN scale has been used to assess biological rhythms in patients with MDD [ 25 27 ]. Using this scale, researchers have observed that biological rhythm disruption is associated with the severity of depression [ 6 , 35 ]. However, to date, no research has examined the reliability and validity of the BRIAN scale in patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…In the present sample, both males and females revealed a mean long DUI, defined by previous reports as >2 years (82), and a significant positive association between DUI and female sex was revealed by the logistic regression. A longer DUI underpins worse BD outcomes, as demonstrated by a higher number of mood episodes, suicide attempts, and hospitalizations (83, 84) and a higher prevalence of psychiatric and medical comorbidities (85,86). Moreover, delayed treatment in affective disorders is associated with a worse response to pharmacological and psychological interventions (87)(88)(89).…”
Section: Discussionmentioning
confidence: 99%
“…A longer duration of untreated depressive illness increases the latency to response [18], meaning that much time is lost in sufferance for the patient. Furthermore, a longer untreated illness duration in depression is associated with a longer overall duration of depression, more comorbidity, more severe depressive symptoms [19], and even higher cognitive impairment [20]. Taken together, these data indicate that the best intervention is early detection [21]; in fact, in more recent years diagnosticians tend to reduce the untreated illness duration and this was followed by reduced time to first pharmacotherapy [22].…”
Section: The Need For Early Detection and Stigma Reductionmentioning
confidence: 99%